Collaspe failure of layered composite pipe - Wong, Chee Kin. (2013)
Every layered composite pipe is designed to ensure safe and reliable performance during its operational life span. Through investigation on the collapse failure of the pipe, unnecessary catastrophic accident can be averted. Apart from safety and reliability, it also promises uninterrupted business operation to the organization.